Terapi Mandi Air Hangat Cinnammon Terhadap Kualitas Tidur Lansia di Posyandu Mawar - Maria Fransiska Ronalia (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Sleeping quality indicates the balance of various aspects of human life. The degradation of sleeping quality often experienced by the elderly people due to many factors happening in the human’s biological body. The purpose of this research is to describe the impact of Cinnammon warm water bathing therapy to the elderlies’ sleeping quality at Posyandu Mawar. The elderly’s sleeping quality is measured using Pittsburg Sleeping Quality Index (PSQI) with 7 categories. And these categories are subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleeping disturbances, use of sleeping medications, and daytime dysfunction over the last month. The sample taken for this research is 28 elderly people. The result of this research presents a significant effect in accordance to its significant value to the data test which uses paired t-test and p value (0,000) <0,05. It concludes that cinnammon warm water bathing therapy gives a significant effect on the improvement of eldersy’s sleeping quality.